O „Rękopisie znalezionym w Saragossie” w perspektywie intertekstualnej raz jeszcze - Kowalewska, Danuta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The monograph of Maria Janoszka, entitled “The Manuscript Found in Saragossa by Jan Potocki and selected novels from the 20th century (Fowles- -Rosendorfer-Gretkowska)” is the first attempt to tackle the problem suggested by the title. Janoszka tries to show the unusual modernity of Potocki’s masterpiece. She researches the intertextual relations between “The Manuscrip”t and three 20th-century novels (“The Magus”, “The Architect of Ruins”, “Rękopis nieodnaleziony, czyli zalety szubienic”). The author focuses on the composition of works, genre and literary conventions. She also analyze the construction of the protagonist and novel spaces. The book is well documented and it has been written in an interesting way, making the monograph an incentive to continue research on Potocki’s masterpiece, which is a pioneering and still inspiring novel.
One More Intertextual Approach to “The Manuscript Found in Saragossa”. The Review of “The Manuscript Found in Saragossa by Jan Potocki and selected novels from the 20th century (Fowles-Rosendorfer-Gretkowska)”
Keywords: The Manuscript Found in Saragossa; Jan Potocki; John Fowles; Herbert Rosendorfer; Manuela Gretkowska; Enlightenment; 20th-century novels; intertextuality; Rękopis znaleziony w Saragossie; oświecenie; powieść dwudziestowieczna; intertekstualność